2021
DOI: 10.21615/cesp.5234
|View full text |Cite
|
Sign up to set email alerts
|

Autogestión: una interpretación analítica conductual

Abstract: La autogestión es un fenómeno que, aunque está presente en varias dimensiones de la vida humana, aún carece de una definición precisa. Es posible identificar diferentes conceptos y usos del término en diferentes áreas del conocimiento. El presente estudio tuvo como objetivo sistematizar el concepto de autogestión basado en la literatura científica de diferentes áreas del conocimiento y, a partir de eso, proponer una definición analítica conductual del fenómeno. Para ello, se realizó una búsqueda bibliográfica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…11 Adherence to self-management among patients with chronic disease is a complicated behavior because many factors are linked and affected by one another. 12 Nevertheless, patients with COPD have insufficient opportunities to engage in the behavior required for selfmanagement as demonstrated in a Birmingham COPD cohort study, 13 which found that less than 50% of patients received advice on diet/exercise, and less than 50% of current smokers were offered practical help to stop smoking in the previous year.…”
Section: Introductionmentioning
confidence: 99%
“…11 Adherence to self-management among patients with chronic disease is a complicated behavior because many factors are linked and affected by one another. 12 Nevertheless, patients with COPD have insufficient opportunities to engage in the behavior required for selfmanagement as demonstrated in a Birmingham COPD cohort study, 13 which found that less than 50% of patients received advice on diet/exercise, and less than 50% of current smokers were offered practical help to stop smoking in the previous year.…”
Section: Introductionmentioning
confidence: 99%